Topical antibacterial medications for therapy of patient with acne - A. G. Pashinjan; A. A. Shahnovich (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Problems of acne pathogenesis are reviewed. Efficacy evaluation and safety use of 1% clindamycin solution at patient with acne are demonstrated.